Category-based grouping in working memory and multiple object tracking. Issue 9 (26th November 2017) - Endress, Ansgar D.; Korjoukov, Ilia; Bonatti, Luca L.
ABSTRACT: Two prominent cognitive capacity limitations are the maximal number of objects we can place in working memory (WM) and the maximal number of objects we can track in a display. Both are believed to have a numeric value of 3 or 4, which has led to the proposal that we have a general cognitive capacity, and that this capacity is most likely linked to limitations of how many objects we can attend simultaneously. Based on previous results showing that we can memorize more objects if they come from different categories than if they come from the same category (e.g., Feigenson & Halberda, 2008; Wong, Peterson, & Thompson, 2008; Wood, 2008), we compare how category-based grouping affects performance for WM and multiple object tracking (MOT). We present participants with either "pure" displays of either cars or faces, or with "mixed" displays of cars and faces. Overall, the effects of category are weak. In some analyses but not others, we replicate the mixed advantage for WM, albeit with a small effect size. In contrast, we observe a weak pure advantage for MOT tasks, at least in a meta-analysis of five experiments, but not in all experiments. Accordingly, WM and MOT tasks differed significantly in their sensitivity to category membership. We also find that WM is slightly better for faces than for cars, but that no such difference exists for MOT. We tentatively suggest that cognitive capacity limitations in different domains are at least partially due to the limitations of distinct mechanisms.